Surgical Outcome of Exvivo Preserved Autologous Cranioplasty - A Novel Approach - Shakya, Bikram; KC, Bidur; Thapa, Amit (Nepal Journal of Neuroscience, 2019)
Autologous cranioplasty is an increasingly common procedure performed in neurosurgical centers following a decompressive craniectomy. Available evidence on the safety of autologous bone flap preservation and cranioplasty is limited due to a large diversity in study conducted, nature of pathology and reported outcomes. In this Institutional Review Board-approved retrospective observational study, patients who underwent neurosurgical intervention as“craniectomy followed by cranioplasty” at the Department of Neurological Surgery, Kathmandu Medical College Teaching Hospital were enrolled retrospectively from 1st May 2012 to 30th April2019. The craniectomy bone flap was preserved exvivo, dipped in spirit solution in deep freeze, then autoclaved prior to cranioplasty. Data were collected from the hospital’s electronic database. Information analyzed included patient age, sex, indication forcraniectomy, interval between craniectomy and cranioplasty, length of hospital stay, peri-operativecomplications and mean time of follow-up. Patients who underwent a cranioplasty following removal of an infected bone flap after a craniotomy were excluded from the study. Associated complications were assessed and statistical analysis was performed using a Fisher’s exact test. There were a total of 210 patients with 92vascular, 58 post traumatic. With all these surgeries undergone we had 9% complication rate, all of whom underwent cranioplasty later than four weeks of primary surgery (p = <0.0001).Ex-vivo preservation and autoclaving of bone flap is a simple technique with significant benefits in our hospital and national scenario with significantly less financial burden to patients